Libraries promoting reflective dialogue in a time of political polarization - Baer, Andrea 1987-; Cahoy, Ellysa Stern; Schroeder, Robert 1953- (Association of College & Research Libraries, 2019)
Reflective dialogue asks us to pause before reacting, to ground ourselves in a sense of compassion for ourselves and others, and to use that grounding to open a space to listen and to speak with the goal of recognizing a shared humanity and appreciating difference. In four sections, Libraries Promoting Reflective Dialogue in a Time of Political Polarization explores the various ways in which librarians experience and respond to political polarization and its effects, both in our everyday work and in our professional communities
Keywords: Politik; Polarisierung; Gesellschaft; Bibliothek; Informationskompetenz; Bürgerbeteiligung; Libraries and society; Library science / Political aspects; Critical thinking; Electronic books; Aufsatzsammlung